The prefoldin‐like protein AtURI exhibits characteristics of intrinsically disordered proteins - Gómez Mínguez, Yaiza (2024)
The prefoldin-like protein UNCONVENTIONAL PREFOLDIN RPB5INTERACTOR (URI) participates in diverse cellular functions, includingprotein homeostasis, transcription, translation, and signal transduction. Thus,URI is a highly versatile protein, although the molecular basis of this versatil-ity remains unknown. In this work, we show that Arabidopsis thaliana(Arabidopsis) URI (AtURI) possesses a large intrinsically disordered region(IDR) spanning most of the C-terminal part of the protein, a feature con-served in yeast and human orthologs. Our findings reveal two key characteris-tics of disordered proteins in AtURI: promiscuity in interacting with partnersand protein instability. We propose that these two features contribute to pro-viding AtURI with functional versatility.